Binary Formation in a 100 μm Dark Massive Core - Shuo Kong; Héctor G. Arce; John J. Tobin; Yichen Zhang; María José Maureira; Kaitlin M. Kratter; Thushara G. S. Pillai (The Astrophysical Journal, 2023)
We report high-resolution ALMA observations toward a massive protostellar core C1-Sa (∼30 M _⊙ ) in the Dragon infrared dark cloud. At the resolution of 140 au, the core fragments into two kernels (C1-Sa1 and C1-Sa2) with a projected separation of ∼1400 au along the elongation of C1-Sa, consistent with a Jeans length scale of ∼1100 au. Radiative transfer modeling using RADEX indicates that the protostellar kernel C1-Sa1 has a temperature of ∼75 K and a mass of 0.55 M _⊙ . C1-Sa1 also likely drives two bipolar outflows, one being parallel to the plane of the sky. C1-Sa2 is not detected in line emission and does not show any outflow activity but exhibits ortho-H _2 D ^+ and N _2 D ^+ emission in its vicinity; thus it is likely still starless. Assuming a 20 K temperature, C1-Sa2 has a mass of 1.6 M _⊙ . At a higher resolution of 96 au, C1-Sa1 begins to show an irregular shape at the periphery, but no clear sign of multiple objects or disks. We suspect that C1-Sa1 hosts a tight binary with inclined disks and outflows. Currently, one member of the binary is actively accreting while the accretion in the other is significantly reduced. C1-Sa2 shows hints of fragmentation into two subkernels with similar masses, which requires further confirmation with higher sensitivity.